Effect of friction reducing devices on wellbore formation - Rini Setiati; Samuel Melvern L P Samosir; Muhammad Taufiq Fathaddin; Priagung Rakhmanto; Oknovia Susanti; Widia Yanti (Universitas Muhammadiyah Magelang, 2025)
Friction is one of the unavoidable factors during drilling. If not properly managed, it can significantly reduce the rate of penetration (ROP), especially in horizontal wells. This research aims to examine the effectiveness of the Friction Reduction Tool (FRT) in managing friction without causing damage to the formation. The FRT is designed to reduce friction between the drill string and the wellbore by minimizing contact. However, its performance is often influenced by two main factors: formation characteristics and drilling parameters. This study analyzes Well X-4, which was drilled without FRT, and Well X-5, which was drilled with FRT from a depth of 2837 m (MD). The analysis focuses on the tool’s impact on stick-slip issues, ROP, and mechanical specific energy (MSE). The results indicate that the use of FRT reduced stick-slip levels and MSE, enabling the drill bit to penetrate the formation more easily. Additionally, activating the FRT from the start increased the penetration rate by 18% compared to drilling without it. These findings suggest that the FRT effectively enhances the drilling rate while preserving the formation integrity.